PENINGKATAN HASIL BELAJAR MATEMATIKA KELAS IV MENGGUNAKAN MODEL TEAM GAMES TOURNAMENT (TGT) - Dhini Putri Aprilia; Dwi Nila Andriani; Purwati, Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the improvement in mathematics learning outcomes regarding multiplication and division of decimal numbers using the Team Games Tournament (TGT) model in class IV students at SD Negeri 01 Klegen. This type of research is PTK. The research design uses the Kimmis and Mc Taggart model. The writing results show that the Team Games Tournament (TGT) model can improve Mathematics learning outcomes for class IV SD Negeri 01 Klegen. The increase in learning outcomes can be seen from the number of students who achieve the KKTP. In pre-action, students who achieved KKTP were 48.27%, in cycle I students who achieved KKTP increased to 72.41%, in cycle II it increased to 82.75% of class IV students who met the criteria for achieving learning objectives. In terms of process, it shows that the quality of the learning process has increased, as seen from students who are more active, communicative, confident and the learning atmosphere is more enjoyable.